Malay Culture-Based Education and Cultural Identity Formation in Early Childhood - Fadillah, Siti; Putri, Azlin Atika; Novitasari, Yesi (Department of Early Childhood Education, Faculty of Education, Universitas Negeri Yogyakarta in in cooperation with in cooperation with the Perkumpulan Pengelola Jurnal PAUD (PPJ PAUD) Indonesia based on the MoU Number: 030/PPJ-PAUD/VIII/2020., 2025)
Cultural identity is a crucial foundation for children’s self development from an early age, especially amid globalization and technological change. This study investigates the relationship between exposure to Malay culture-based education in Early Childhood Education (ECE) and the cultural identity formation of children aged 5-6 years in Pekanbaru City. A quantitative correlational design was applied, using questionnaires distributed to teachers and parents from four ECE institutions. The sample was selected through purposive sampling, involving respondents directly engaged in Malay culture-based learning. Data were analyzed using Pearson correlation. The results show a significant positive relationship between Malay cultural exposure and cultural identity (r = 0.62; p < 0.01). These findings highlight the theoretical importance of integrating sociocultural perspectives in early childhood education and the practical implication of embedding local culture through language, folklore, pantun, and traditional games to strengthen cultural identity.